Historians and Slavery: A Critical Analysis of Perspectives and Irony in American Slavery, and Other Recent Works. - Wright, W. D. (1978)
Keywords: Genovese, Eugene D., 1930-2012; Engerman, Stanley L; Perspectives and irony in American slavery; Slavery; Historiography; United States; dept.his; faculty_collection

Nietzsche and eschatology - Ausmus, Harry J. (The Journal of Religion, 1978)
Keywords: dept.his

Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
Keywords: book.review; dept.his

Review of The Encyclopaedia Africana Dictionary of African Biography, Volume I: Ethiopia-Ghana - Feinberg, Harvey M. (The International Journal of African Historical Studies, 1978)
Keywords: dept.his

Plant Liberation - Struggle Against Fauna Chauvinism - Tyler, RL (Humanist, 1978)
Keywords: dept.his; ⛔ No DOI found